(3TQM cJGH GdLeds - (3eLghds
(3ChdgG (B:s
(3GdKGdK dCiTF bGd (B: (3hMQa LGA deYfi , aNU GdMQa HeLjFI deYfi Ohf GdGSe hGdaYd hcd hGMO efgeG bO LGA deYfi s
(3BNQgG (B:s
(3EPG bUQJ CSjGafG cGf hUdgG NWGfG Edi CYOGFfG afVGQH Lhe fVGQH HGdYWa Ydjg , aGage JYde , hbS fUH Ef TGA Gddg JYGdi Je GdSaQ GdChd ef GdJaSjQ Ydi cJGH GdLed hGdMeO ddg hMOg hUdhGJg Ydi SjOfG eMeO hUMHg hSde JSdjekG cKjQkG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Hg eWGdH ddcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs